Chemical and morphological characterization by SEM–EDS of PM2.5 collected during winter in Ulaanbaatar, Mongolia. (15th June 2023) - Park, Ji-In; Kim, Min Sung; Yeo, Myoung; Choi, Mira; Lee, Ji Yi; Natsagdorj, Amgalan; Kim, Changhyuk; Song, Mijung; Jang, Kyoung-Soon
Abstract: In this study, the morphological and elemental properties of airborne fine particles (PM2.5 ) collected during winter (15 December 2020–14 January 2021) in Ulaanbaatar, Mongolia, were investigated using scanning electron microscopy (SEM) combined with energy-dispersive X-ray spectrometry (EDS). SEM analysis of the PM2.5 samples revealed that the particle shape distribution on haze days (daily mean PM2.5 concentration of over 100 μg m −3 ) was irregular (62%), spherical (24.6%), cluster (10.7%), and chain-like (2.7%), while the particle shape on clean days (daily mean PM2.5 concentration of less than 30 μg m −3 ) was distributed as follows: irregular (56%), cluster (22%), spherical (17.3%), and chain-like (4.7%). The apparent mean particle size on haze days (2.07 μm) was twofold greater than that on clean days (1.13 μm). Based on the EDS spectra, carbonaceous particles were the most abundant (38%), followed by mineral dust (36%), Fe-rich particles (4.7%), N-rich particles (4.7%), calcium sulfate (4%), fly ash (4%) and others (2%) on clean days. On haze days, carbonaceous particles accounted for 86% of the total, and Fe-rich, mineral, transition metal, and calcium sulfate particles accounted for 6.7, 4.7, 1.3 and 0.7%, respectively, indicating that carbonaceous particles were the main contributor on haze days. In particular, the sample filters collected on haze days were predominantly covered with tar/soot-like sticky matter, in contrast to those collected on clean days. Spearman's rank correlation analysis of PM2.5 with inorganic gaseous components as well as meteorological conditions further revealed that high levels of PM2.5 in winter in Ulaanbaatar were significantly associated with SO2 (ρ = 0.95), and CO (ρ = 0.94). These associations indicated that ambient SO2 and CO gases are indicative of haze episodes during the study period, and suggested a strong contribution of solid fuel combustion producing those gases in Ulaanbaatar during winter. Graphical abstract: Image 1 Highlights: Morphological and elemental properties of PM2.5 in Ulaanbaatar was investigated. Tar/soot-like sticky matter was abundantly observed on the sample filters of haze days. Apparent mean particle size on haze days was twofold greater than that on clean days. Ambient SO2 and CO gases are indicative of haze episodes in Ulaanbaatar during winter.